Implementation of Hygiene Education through Community Empowerment for Effective Dengue Hemorrhagic Fever Prevention: Case Study in RW 4 Penagagan Village - Tati Nuryati; Handayani; Rahmatun Phounna; Wida Feriningsih; Shirley Christine; Uswatun Hasani; Juanda Izhar; Fitria Ramdhita (Jurnal Serambi Ilmu, 2024)
To improve the cleanliness of the community's environment, counseling was provided on Dengue Prevention and Mosquito Nest Eradication (PSN). Thus, the UHAMKA Partner Cooperation Program (PKM) provides community empowerment solutions regarding Triggering Dengue Prevention and Mosquito Nest Eradication (PSN). The purpose of this community empowerment is to increase public knowledge in the prevention of dengue and the eradication of mosquito nests, among others, through the 3M Plus Movement (Draining, Closing, Recycling), raising larvae-eating fish, using mosquito nets while sleeping, and using mosquito repellents, Fogging: Spraying mosquitoes using insecticides, Giving abate: Larvicide to kill mosquito larvae in water reservoirs and KIE (Communication, Information, and Education): Increasing public awareness about dengue fever and how to prevent it. Before the dengue triggering activity was carried out, respondents were asked to fill out a knowledge questionnaire. The total number of respondents who filled out the questionnaire was 22 respondents. Respondents were asked to fill out a pre-test questionnaire before triggering dengue fever and to fill out a post-test questionnaire again after triggering dengue. The results of the respondents' characteristics showed that there were 16 respondents (72.7%) more female than 6 (27.3%) males. Respondents aged < 40 years were 7 respondents (31.8%) less than respondents aged > 41 years as many as 15 respondents (68.2%). And based on education level, respondents with higher education level (≥SMA) as many as 6 people (27.3%) were less than respondents with low education level (≤ junior high school) as many as 16 people (72.7%). The results of the distribution of respondents based on the Pre- Test knowledge variable showed that 11 respondents (50%) had high knowledge and 11 people (50%) had low knowledge. And the results of the distribution of respondents based on the Post-Test knowledge variable showed that 13 respondents (59.1%) had high knowledge more than 9 people (40.9%) who had low knowledge. The above results show that by making efforts to increase community knowledge by organizing and community development, triggering activities are more effective than simple counseling/lectures. Triggering makes respondents more active, not easily bored, and easy for respondents to remember.